2006
DOI: 10.1209/epl/i2005-10523-2
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing transitions on microtextured materials

Abstract: A drop of water thrown on a super-hydrophobic solid will often bounce off. Here we discuss the conditions to be fulfilled on the surface design (which provides superhydrophobicity) to observe such a behavior. This allows us to precise how a material can be made water-repellent. We show in particular how the reduction of the scale of the microstructure provides a robust water repellency, and describe some peculiarities of violent shocks on such surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
388
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(410 citation statements)
references
References 15 publications
16
388
5
1
Order By: Relevance
“…Although a number of simpler models than Maitra's model (Equation 2) have been proposed in order to predict the pinning threshold based on balancing PL with either the dynamic or water hammer pressure, these models do not include the effect of the droplet diameter [15,38,39]. From our own experiments, we observed that water droplets of larger diameter are significantly more prone to pinning than smaller droplets, which is demonstrated in supporting Figure S4, in which one large droplet exhibits partial rebounding behaviour, while two smaller droplets concurrently exhibit complete rebounding.…”
Section: The Impalement Transition On Superhydrophobic Surfacesmentioning
confidence: 99%
“…Although a number of simpler models than Maitra's model (Equation 2) have been proposed in order to predict the pinning threshold based on balancing PL with either the dynamic or water hammer pressure, these models do not include the effect of the droplet diameter [15,38,39]. From our own experiments, we observed that water droplets of larger diameter are significantly more prone to pinning than smaller droplets, which is demonstrated in supporting Figure S4, in which one large droplet exhibits partial rebounding behaviour, while two smaller droplets concurrently exhibit complete rebounding.…”
Section: The Impalement Transition On Superhydrophobic Surfacesmentioning
confidence: 99%
“…If the gravitational forces acting on the solid-liquid contact overcome the shear forces, the SL contact gets de-pinned from the apex of the roughness feature, and the corresponding mechanism is called depinning (figure 1b) 20,37 figure 2i and figure 2ii). On the other hand, case IV consists of an energetically favorable Wenzel state, i.e.…”
Section: Metastable Cassie State: Geometric Orientationmentioning
confidence: 99%
“…The value of k approaches a maximum value of 0.5 for nearly elastic collisions 48 . The experiments on droplet impingement typically use a droplet speed of the order of ms -1 , for which the water hammer coefficient is typically approximated as 0.2 20,22,49 . For low velocities and high droplet volumes, the collision is known to be inelastic, which lowers the coefficient k to the order of 0.001 (equation 23) 18 .…”
Section: Surface Design For Quasi-static Robustness: Pressure Balancementioning
confidence: 99%
“…According to the Washburn's law for pressure entry in porous media [23], the order of magnitude of the entry pressure is inversely proportional to the typical size R of roughness: P w = 2γ cos θ/R. The quantitative measurements obtained on periodic arrays of micro-pilars evidenced that R ∼ s 2 L [18,19], with s and L stand for the space between pillars and their length, respectively. Therefore, our idea is to increase robustness by covering the surface with a forest of chemically-grown SiNWs of high aspect-ratio (from 30 to 100) and of about 50 to 100 nm in diameter, see Fig.…”
Section: Qualitative Analysis Of the Robustness Of A Surfacementioning
confidence: 99%
“…Drop impact experiment is a particularly versatile way to test this robustness [18][19][20][21][22]. During impact, the sudden vertical deceleration of the liquid particles leads to momentum transfer that applies an effective dynamical pressure P dyn = 1/2ρU 2 , with U being the impact velocity and ρ the liquid density.…”
Section: Qualitative Analysis Of the Robustness Of A Surfacementioning
confidence: 99%